False vacuum decay in quantum spin chains - Humar, Gregor (Matrika, 2022)
False vacuum decay has been at the centre of physics research in cosmology and quantum field theory. As the timescales and the dynamics of this phenomenon are difficult to observe and describe analytically, there have been only limited options for its study. With advancements in condensed matter physics and quantum technologies the study of false vacuum decay is becoming more accessible. Metastable systems, with dynamics analogue to the false vacuum decay, can be observed on timescales that allow measurements. In particular, the transverse Ising model can present metastable decay in non-equilibrium dynamics following a quantum quench. Numerical simulations show vacuum decay on short timescales. This presents an opportunity for further study on longer timescales using quantum annealing devices.
Keywords: condensed matter physics; false vacuum; fizika kondenzirane snovi; kvantna mehanika; lažni vakuum; quantum mechanics; vacuum; vakuum